Probiotic Lactobacillus rhamnosus GR-1 supplementation attenuates Pb-induced learning and memory deficits by reshaping the gut microbiota - Gu, Xiaozhen; Bi, Nanxi; Wang, Tian; Huang, Chengqing; Wang, Rongrong; Xu, Yi; Wang, Hui-Li (Frontiers in Nutrition, 2022)
Lead (Pb) exposure during early life has been associated with an increased risk of neurodevelopmental disorders, including learning and memory deficits. The intestinal flora, via the microbiome-gut-brain axis, could play a significant role in the nervous system. However, it is far from clear that the effects of probiotics on ameliorating Pb-induced learning and memory deficits. Here, we show that adolescent Pb exposure (150ppm) for two months impaired spatial learning and memory ability, accompanied by the decreasing diversity of gut microbiota, and the decreasing abundance of lactobacillus at the genus level. Surprisingly, administration of the Lactobacillus rhamnosus GR-1 (1010 organisms/rat/day), not Lactobacillus rhamnosus LGG or Lactobacillus reuteri RC-14, reversed learning and memory deficits induced by Pb exposure. Meanwhile, administration of the Lactobacillus rhamnosus GR-1 increased the diversity of the gut microbiota composition, and partially normalized the genus level of Lactobacillus, Parabacteroides, Enterococcus, Akkermansia in Pb-exposed rats. Notably, supplementation of Lactobacillus rhamnosus GR-1 decreased the gut permeability of Pb-exposed rats, reduced proinflammatory cytokines (interleukin-1β (IL-1β) and IL-6) expression, promoted anti-inflammatory cytokines (G-CSF) expression. Interestingly, neural cell treatment with G-CSF rescued Pb-induced neurotoxicity. In general, Lactobacillus rhamnosus GR-1 supplementation recovered the Pb-induced loss of intestinal bacteria (Lactobacillus), which may have reversed the damage of learning and memory ability. Collectively, our findings demonstrate an unexpectedly pivotal role of Lactobacillus rhamnosus GR-1 in Pb-induced cognitive deficits and identify a potential probiotic therapy for cognitive dysfunction during early life.